2013
DOI: 10.1136/jmedgenet-2013-102001
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the T (brachyury) gene cause a novel syndrome consisting of sacral agenesis, abnormal ossification of the vertebral bodies and a persistent notochordal canal

Abstract: We have identified a shared homozygous mutation in three families in T and linked it to a novel syndrome consisting of sacral agenesis, a persistent notochordal canal and abnormal ossification of the vertebral bodies. We suggest that screening for the ossification of the vertebrae is warranted in patients with sacral agenesis to evaluate the possible causal involvement of T.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
39
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 33 publications
2
39
0
2
Order By: Relevance
“…The inheritance pattern for NTD has long been suggested to exemplify multifactorial inheritance. However, Postma and colleagues have recently reported on the involvement of T (brachyury) gene in the pathogenesis of an apparently monogenic form of NTD in humans encompassing sacral agenesis, abnormal ossification of the vertebral bodies and a persistent notochordal canal (Postma et al 2013). This is consistent with available data on the role of T in vertebral development (Ghebranious et al 2008;Kromik et al 2015).…”
supporting
confidence: 52%
“…The inheritance pattern for NTD has long been suggested to exemplify multifactorial inheritance. However, Postma and colleagues have recently reported on the involvement of T (brachyury) gene in the pathogenesis of an apparently monogenic form of NTD in humans encompassing sacral agenesis, abnormal ossification of the vertebral bodies and a persistent notochordal canal (Postma et al 2013). This is consistent with available data on the role of T in vertebral development (Ghebranious et al 2008;Kromik et al 2015).…”
supporting
confidence: 52%
“…Additionally, these papers provide illustrations as the existence of multiple genetic mechanisms in patterning genes which may act to produce a vertebral malformation. The families reported by Postma et al 1 are consistent with recessive inheritance. The families reported by Ghebranious et al 2 and Papapetrou et al 3 are illustrative of decreased penetrance as the parents of each affected offspring had the identical c.1013 C>T mutation but were clinically asymptomatic.…”
mentioning
confidence: 73%
“…We have read the paper by Postma et al 1 in the recent Journal of Medical Genetics describing a homozygous missense mutation, p.H171R T(brachyury) in three consanguineous families with sacral agenesis, persistent notochord and abnormal ossification of vertebral bodies. We would like to point out that our group has previously described the same heterozygous mutation (c.1013 C>T) in three patients with vertebral malformations including sacral agenesis, cervical vertebral malformations and cervical and thoracic vertebral malformations 2.…”
mentioning
confidence: 99%
“…The genetic analysis, published by Postma et al [10], identified a homozygous single base-pair substitution (c.796A>G) in the T gene, in all four affected individuals. All parents were heterozygous for this mutation, and all their unaffected sibs were either heterozygous or wild type.…”
Section: Discussionmentioning
confidence: 99%
“…All parents were heterozygous for this mutation, and all their unaffected sibs were either heterozygous or wild type. The nucleotide substitution resulted in a mutant protein with reduced activity [10]. …”
Section: Discussionmentioning
confidence: 99%